How voters assess elite-educated politicians: A survey experiment. (December 2018) - Gift, Thomas; Lastra-Anadón, Carlos X.
Abstract: Are politicians with elite backgrounds more electable? In this article, we test whether being an elite is a net positive or negative in running for public office via an original survey experiment that manipulates one of the most salient indicators of eliteness in American life: university education. We find that liberals, but not conservatives, perceive politicians who attended elite schools to be more competent. Meanwhile, conservatives, but not liberals, perceive politicians who attended elite schools to be less relatable. On average, citizens are mildly, but not significantly, less inclined to vote for elite-educated politicians. By embedding treatments in our survey for whether politicians came from advantaged or disadvantaged upbringings, we also confirm that our results do not entirely reflect generic attitudes toward economically privileged candidates.